Influence of gender on the clinical outcomes of Asian non-valvular atrial fibrillation patients: insights from the prospective multicentre COOL-AF registry - Arintaya Phrommintikul; Rungroj Krittayaphong; Arjbordin Winijkul; Komsing Methavigul; Chulalak Komoltri; Pontawee Kaewkumdee; Ahthit Yindeengam (BMJ Open)
Objective To determine the effect of gender on clinical outcomes of Asian non-valvular atrial fibrillation patients.Design This is a cohort study.Setting 27 university and regional hospitals in Thailand.Participants Patients with non-valvular atrial fibrillation.Primary and secondary outcomes measures The clinical outcomes were ischaemic stroke/transient ischaemic attack (TIA), major bleeding, intracerebral haemorrhage (ICH), heart failure and death. Follow-up data were recorded every 6 months until 3 years. Differences in clinical outcomes between males and females were determined. Multivariate analysis was performed to assess the effect of gender on clinical outcomes. Survival analysis and log-rank test were performed to determine the time-dependent effect of clinical outcomes, and the difference between males and females. Effect of oral anticoagulant (OAC) on outcomes and net clinical benefit of OAC was assessed. The analysis was performed both for the whole dataset and propensity score matching with multiple imputation.Results A total of 3402 patients (mean age: 67.4±11.3 years; 58.2% male) were included. Average follow-up duration 25.7±10.6 months (7192.6 persons-year). Rate of ischaemic stroke/TIA, major bleeding, ICH, heart failure and death were 1.43 (1.17–1.74), 2.11 (1.79–2.48), 0.70 (0.52–0.92), 3.03 (2.64–3.46) and 3.77 (3.33–4.25) per 100 person-years. Females had increased risk for ischaemic stroke/TIA and heart failure and males had increased risk for major bleeding and ICH. Ischaemic stroke/TIA risk in females and major bleeding and ICH risk in males remained even after correction for age, comorbid conditions and anticoagulation treatment. OAC reduced the risk of ischaemic stroke/TIA in males and females, and markedly increased the risk of major bleeding and ICH in males.Conclusions Females had a higher risk of ischaemic stroke/TIA and heart failure, and a lower risk of major bleeding and ICH compared with males. OAC reduced risk of ischaemic stroke/TIA in females, and markedly increased risk of major bleeding and ICH in males.